Kajian Dampak Tata Guna Lahan terhadap Kinerja dan Biaya Tundaan Simpang (Studi Kasus : Simpang Tiga Jl. GOR – Jl. A. Yani, Kota Blora) - Hartono Guntur Ristiyanto (SIMETRIS, 2021)
The current land use have made the corridor of Jalan GOR in Blora Regency plays an important role in the aspect of transport demand. The area’s development must be balanced with the adequate transport supply in such a way that it will minimize the negative impact due to the imbalance between demand and transport supply. One of the existing transport supply is an unsignalized intersection at the eastern end of the corridor. The potential problem due to the existence of nearby land uses, such as gas stations, on intersection performance is : the presence of delays. Based on those research backgrounds, the formulation of the research problem is: how does the existence of gas station affect the intersection performance and the cost of delay? This research aims to analyze the performance of intersections due to the existence of gas stations. The results of the analysis show that the existence of gas station gives various contribution to intersection performance parameters. Respectively, the biggest effect occurred on the increase in vehicle volume, degree of saturation, and total delay (especially traffic delay). Overall, the existence of a gas station has no effect on the level of service’s value of the intersection. Meanwhile, the value of the highest delay costs occurs during the peak hours of the day. The predicted intersection performance without any geometric improvement for 5 years will begin to decline in third year. Meanwhile, if the intersection is widened, it will begin to decline in the fourth year. However, this geometric improvement has only a very small effect on intersection performance.